PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN UMKM NUGGET SEBAGAI PROGRAM KEWIRAUSAHAAN MASYARAKAT DI DESA GLANDANG KECAMATAN BANTARBOLANG - Riandita, Lilik (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2024)
The purpose of this activity is to empower the community's economy by providing socialization and training on processing corn into nuggets, so as to increase the income of the people in Glandang Village. This activity was carried out by providing training and assistance to the people of Glandang village in making corn nuggets. It is hoped that with this entrepreneurship program, people can take advantage of the potential of natural resources around them and improve their economic welfare. With the socialization of making corn nuggets, communication and relationships are created that are getting closer and can help villagers in processing corn in Glandang Village, Bantarbolang District, Pemalang Regency.